The characteristics and trends of historical writing in the People’s Republic of China since 1978 - Zhang, Xupeng (Historein, 2014)
The December 1978 decision at the third plenary session of the eleventh central committee of the Chinese Communist Party to implement reform and opening-up marks an important watershed in historical studies in contemporary China. With this in mind, historical studies in contemporary China can be conveniently subdivided into three periods: the period from the founding of the People’s Republic of China to the start of the Cultural Revolution (1949–1966); the Cultural Revolution period (1966–1976); and the period starting with reform and opening-up, or the “new period” (1978 onwards). This paper gives a comprehensive survey on historical writing in the People’s Republic of China since 1978. The paper has three parts. The first is about how and why Chinese historians have turned away from traditional political history to cultural and social histories. The second part analyses four paradigms in contemporary historical research in China: the revolutionary history paradigm, modernisation paradigm, postmodern paradigm and global history paradigm. The third part reviews world history studies in China and lists four methods that have successively been employed, namely total/integral history, modernisation history, the history of civilisational exchange and global history. The paper concludes that it is incumbent on Chinese historians to be sensitive to all foreign historiographies while steadfastly adhering to the best Chinese traditions, for only in this way can a unique and worthy model of Chinese historiography emerge.